Germany: Policy-Making strategies and project experiences : chapter 19 - Härtel, Michael [Verfasser] (My University, 2009)
"This chapter aims to help concretize the debate on how to achieve the objectives associated with the principle of sustainability, and to describe how vocational education and training can contribute to this process. A case-study approach to the topic has been chosen deliberately, so that concrete experiences and examples are used to illustrate ways of operationalizing the formulated policy objectives and achieving process-based implementation." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; I 1 Internationale Berufsbildung; L 4.2.4 Expertennetzwerke / Wissensplattformen; Nachhaltige Entwicklung; Berufsbildungspolitik; Berufsausbildung; Internationale Zusammenarbeit; Netzwerk